Sistem Pendukung Keputusan untuk Menentukan Karyawan Terbaik dengan Metode TOPSIS pada PT. Sumbertama Nusa Pertiwi - mayang ruza; ibnu sani wijaya; eddy suratno (Jurnal Manajemen Informatika JAMIKA, 2023)
PT. Sumbertama Nusa Pertiwi is a company engaged in palm oil plantations and processing. In carrying out the operations of PT. Sumbertama Nusa Pertiwi gives awards to employees by selecting the best employees every year. This research aims to design a decision support system to identify the best employees at PT. Sumbertama Nusa Pertiwi by giving a rating to each employee using the Technique for Other Reference by Similarity to Ideal Solution (TOPSIS) method. The results of this research are a decision support system using the TOPSIS method with ten criteria, namely work performance, attitudes and ethics, motivation, initiative, loyalty, responsibility, discipline, honesty, leadership, and safeguarding company assets. As an alternative, there are five employees, namely Sutrisno, M. Ahyar, Lamidi, Sabar, and Iskandar. With the first rank, namely Sabar with a value of 0.61886, Iskandar with a value of 0.537845, M. Ahyar with a value of 0.529544, Sutrisno with a value of 0.484994, and finally Lamidi with a value of 0.449489. So, the aim of designing a decision support system using the TOPSIS method is to make it easier for companies to determine the ranking of the best employees at PT. Sumbertama Nusa Pertiwi.